Clinical characteristics and efficiency of antidepressant therapy of mood disorders with comorbid alcohol use disorder - O. V. Roshchina; A. I. Rozin; E. D. Schastnyy; N. A. Bokhan (Бюллетень сибирской медицины)
Aim. To determine the nosological and clinical features of mood disorders (MD) with comorbid alcohol use disorder (AUD) and efficiency of antidepressant therapy.Materials and methods. We examined 88 patients with MD and comorbid AUD – 33 females (37.5%) and 55 males (62.5%). The first group included 31 patients with AUD without comorbid affective symptoms, the second group contained 29 patients with MD without AUD, the third group included 28 patients with AUD and MD. In the study, we applied clinical-psychopathologic, clinical-dynamic, and statistical methods with Pearson’s χ2 test, Mann – Whitney U-test (for comparison of independent samples), Kruskal – Wallis test (for more than two independent samples), and Wilcoxon test (for comparison of dependent samples). At the level of statistical  significance, no differences between the groups according to the gender – age composition were revealed (p = 0.115 – according to gender composition, р = 0.248 – according to age composition, Pearson’s χ2 test).Results. The patients with the diagnosis of AUD with comorbid MD showed worse dynamics of the reduction of depressive [from 24.0 (18.3; 33.0) to 9.0 (4.3; 12.0) points according to the Structured Interview Guide for the Hamilton Depression Rating Scale – Seasonal Affective Disorder (SIGH-SAD)  (р = 0.001, Wilcoxon test)] and anxiety [from 20.5 (12.5; 25.0) to 5.5 (3.3; 8.0) points according to the Hamilton Anxiety Rating Scale (HARS) (р = 0.001, Wilcoxon test)] symptoms against the background of the therapy with initially lower indices compared to the group with MD alone [from 27.0 (21.0; 36.0) to 6.0 (5.0; 11.0) points according to SIGH-SAD (р = 0.001, Wilcoxon test) (intergroup differences upon admission р = 0.046; upon  discharge р = 0.683, Mann – Whitney U-test) and from 21.0 (14.0; 29.0) to 5.0 (3; 10.5) points according to HARS (р = 0.001, Wilcoxon test) (intergroup differences upon admission р = 0.082; upon discharge р = 0.825, Mann –  Whitney U-test)]. The course of AUD is characterized by a larger extent of malignancy in the group with a comorbidity: decrease in pathological  alcohol craving from 31.5 (16.3; 43.5) points to 8 (2.3; 14.8) (р = 0.001, Wilcoxon test) in the group with a comorbidity and from 29.5 (21.8; 37.0) to 7 (3.0; 11.3) points with AUD alone (р = 0.001, Wilcoxon test) (intergroup  differences upon admission р = 0.058; upon discharge р = 0.04, Mann – Whitney U-test on the Obsessive Compulsive Drinking Scale (OCDS).Conclusion. Clinical-dynamic characteristics of MD with comorbid AUD  result in therapeutic difficulties associated with comparatively worse dynamics of reduction of the symptoms of both diseases.